2019
DOI: 10.1177/0194599819866819
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Intraoperative Parathyroid Hormone and Calcium in the Treatment of Tertiary Hyperparathyroidism

Abstract: Objective Tertiary hyperparathyroidism, an autonomous hyperproduction of parathyroid hormone (PTH), has a challenge in its treatment. This study asked whether the intraoperative PTH and calcium drop can confirm the resection of all parathyroid tissues. Study Design Case series with planned data collection. Setting Tertiary referral medical center. Subjects and Methods The study assessed patients with tertiary hyperparathyroidism who were treated at the Hospital of the State University of Campinas from 2007 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…356,359 Failure to decline may indicate the presence of ectopic or supernumerary glands. 358,359 Lastly, the rates of persistent and recurrent disease declined when ioPTH was employed during PTX when compared with operations where ioPTH was not used. 340 Recommendation 6-14: The benefits and limitations of ioPTH monitoring in patients with THPT should be understood by all surgeons performing these operations.…”
Section: Tertiary Hpt: Criteria For Iopth Decline and Utility Of Iopt...mentioning
confidence: 99%
See 1 more Smart Citation
“…356,359 Failure to decline may indicate the presence of ectopic or supernumerary glands. 358,359 Lastly, the rates of persistent and recurrent disease declined when ioPTH was employed during PTX when compared with operations where ioPTH was not used. 340 Recommendation 6-14: The benefits and limitations of ioPTH monitoring in patients with THPT should be understood by all surgeons performing these operations.…”
Section: Tertiary Hpt: Criteria For Iopth Decline and Utility Of Iopt...mentioning
confidence: 99%
“…Conversely, other author groups concluded that ioPTH testing impacted the real-time operative care of THPT as ioPTH assays allow for limited rather than subtotal resections in 9% to 20% of patients 356,359. Failure to decline may indicate the presence of ectopic or supernumerary glands 358,359. Lastly, the rates of persistent and recurrent disease declined when ioPTH was employed during PTX when compared with operations where ioPTH was not used 340…”
Section: Planning Of Surgerymentioning
confidence: 99%
“…In tertiary HPT, the parathyroid glands become autonomous in the production of PTH, despite the improvement in renal function, observed mainly in post-kidney transplant patients [36]. There is not a sufficient decrease in PTH, which remains in the range of 5-10 times greater than normal.…”
Section: Diagnosismentioning
confidence: 99%
“…Vitamin D levels also tend to normalize, since the absence of kidney damage in the post-transplant patient normalizes the conversion of vitamin D into its active form (calcitriol) and also normalizes the intestinal absorption of calcium. Thus, the mechanisms lead to increased serum calcium concentration [36,37].…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation